2022
DOI: 10.1371/journal.pone.0262200
|View full text |Cite
|
Sign up to set email alerts
|

The Jack and Jill Adaptive Working Memory Task: Construction, Calibration and Validation

Abstract: Visuospatial working memory (VSWM) is essential to human cognitive abilities and is associated with important life outcomes such as academic performance. Recently, a number of reliable measures of VSWM have been developed to help understand psychological processes and for practical use in education. We sought to extend this work using Item Response Theory (IRT) and Computerised Adaptive Testing (CAT) frameworks to construct, calibrate and validate a new adaptive, computerised, and open-source VSWM test. We aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 94 publications
(131 reference statements)
1
13
0
Order By: Relevance
“…6 The test length on the LongGold project was set to eight trials. In the present study, the participants completed a total of 7 trials for the JAJ since in the original study the authors found that reliability and validity for this test are acceptable after 7 or 8 trials (5–6 mins), with diminishing gains from more trials ( Tsigeman et al, 2022 ).…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…6 The test length on the LongGold project was set to eight trials. In the present study, the participants completed a total of 7 trials for the JAJ since in the original study the authors found that reliability and validity for this test are acceptable after 7 or 8 trials (5–6 mins), with diminishing gains from more trials ( Tsigeman et al, 2022 ).…”
Section: Methodsmentioning
confidence: 75%
“…To administer the tests, we employed the psychTestR online testing framework ( Harrison, 2020 ). Several adaptive ability tests have been developed in this framework, including the melody discrimination test (MDT; Harrison et al, 2017 ), the beat perception test (BAT; Harrison and Müllensiefen, 2018 ), the mistuning perception test (MPT; Larrouy-Maestri et al, 2019 ), the visuospatial WM test (JAJ; Tsigeman et al, 2022 ), and the rhythmic ability test (RAT; MacGregor et al, 2022 ). In this study we used a selection of tests and questionnaires as follows, summarized also in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This assesses fluid intelligence, non-verbal reasoning and problem solving through asking subjects to complete visual puzzles similar in style to Raven's Matrices (Chan & Kosinski, 2015). Additionally, visuo-spatial working memory was measured using a Working Memory Test which required participants to remember the positions of colored balls in the hands of two cartoon characters (Tsigeman et al, 2022).…”
Section: General Cognitive Measuresmentioning
confidence: 99%